Is ballistic transportation or quantum confinement responsible for changes in the electrical properties of thin polymer films? - Veder, Jean-Pierre; Patel, Kunal; Lee, Junqiao; Alam, M.; James, M.; Nelson, A.; De Marco, Roland (R S C Publications, 2013)
Resistivities of thin polymer films increase abruptly with decreasing thickness, although the corresponding decline in resistance plateaus below a certain thickness. One can jump to the incorrect conclusion that quantum confinement and surface scattering are responsible for this behaviour, and we highlight the pitfalls of committing such an error.